Netflix incorporates advertising into its business model: Pre-roll and the alliance with Microsoft as a solution to its stock market debacle - García-Chamizo, Fernando; Miranda García, Javier (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Netflix lost 1,170,000 subscribers and tens of millions of dollars in the stock market in the first half of 2022, when it expected an increase of 2.5 million subscribers in the first quarter of the year and a plunge of two million in the second half. This stock market debacle has led the company to adapt its business model by scheduling the launch of a cheaper subscription with digital advertising with Microsoft, with which it hopes to recover one million subscribers between July and September 2022. This article looks at the advertising alternatives Netflix can use.